Financial Derivatives : A Supplement to the Fifth Edition of the Balance of Payments Manual. (Manuals and Guides; MG, 2000)
In the late 1990s, international statistical experts confirmed that financial derivatives should be treated as financial assets and that transactions in financial derivatives should be reported as separate transactions rather than as integral parts of the values of underlying transactions or of financial assets to which some derivatives are linked as hedges. Therefore, to parallel revisions made to the System of National Accounts (1993), an addendum and amendments to the fifth edition (1993) of the Balance of Payments Manual (BPM5) were prepared and published, in early 2000, as a supplement entitled Financial Derivatives. This supplement comprises two parts. Part I contains a new chapter in which the features of financial derivatives and treatments appropriate for specific derivatives were described. Part II consists of modifications to those portions of the BPM5 that pertain to financial derivatives. The revisions are shown by means of shading and strikeout. Financial Derivatives is an essential component of the BPM5.